2009
DOI: 10.1038/ajh.2008.346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Asymmetric Dimethylarginine and Homocysteine in Microangiopathy-Related Cerebral Damage

Abstract: ADMA and tHcy levels were studied in 712 subjects with or without MARCD. The Arg/ADMA ratio was suggested to be an independent risk factor for MARCD. A large-scale prospective study is warranted to confirm the causal relationship between Arg/ADMA and MARCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…In CHF, elevated levels of ADMA concurred with disease severity, and ADMA was suggested as a pathological link for impaired vasodilator capacity [31]. In acute stroke, increased ADMA levels were observed in cardioembolic infarctions, transient ischemic attacks and microangiopathy-related cerebral damage [9,32]. In our study, patients with cardioembolic ischemic stroke displayed elevated ADMA levels as well as diminished L -arginine/ADMA ratios that were associated with reduced vasodilatation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In CHF, elevated levels of ADMA concurred with disease severity, and ADMA was suggested as a pathological link for impaired vasodilator capacity [31]. In acute stroke, increased ADMA levels were observed in cardioembolic infarctions, transient ischemic attacks and microangiopathy-related cerebral damage [9,32]. In our study, patients with cardioembolic ischemic stroke displayed elevated ADMA levels as well as diminished L -arginine/ADMA ratios that were associated with reduced vasodilatation.…”
Section: Discussionmentioning
confidence: 83%
“…Elevation of plasma ADMA concentration and a decreased L -arginine/ADMA ratio correlate with endothelial-dependent flow-mediated dilatation (FMD) in hypercholesterolemia, hyperhomocysteinemia and hypertriglyceridemia [7,8]. In cerebrovascular research, an independent association of the L -arginine/ADMA ratio with microangiopathy-related cerebral damage was shown in 712 patients [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Such low L-arginine/ ADMA ratio is associated with lacunar infarctions in patients with Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL). 51,52 Interestingly, we observed a transient elevation of the L-arginine/ADMA ratio at 24 poststroke hours suggesting that a temporary increase of L-arginine along with decrease of ADMA might be a protective mechanism. It has been shown previously that ADMA increased vascular stiffness and decreased cerebral perfusion in healthy subjects.…”
Section: Discussionmentioning
confidence: 85%
“…49,73 In all the studies in which ADMA levels were measured, an independent association with both lacunar infarcts and WMH was reported. 54,55,78 Matrix metalloproteinase 9 (MMP9) was measured in a total of 234 patients, but the association with WMH was significant only at univariate analyses. 69,70 The Northern Manhattan Study found an independent association of both MPO and Lp-PLA2 with WMH, but the result for Lp-PLA2 was not confirmed in the Framingham Offspring Study.…”
Section: 61mentioning
confidence: 99%